Вплив часових інтервалів у транспортному потоці на пропускну здатність - Ройко, Юрій; Санько, Ярослав; Євчук, Мирослав (Видавництво Львівської політехніки, 2015)
Search reserve capacity in terms of sustainable urban development is one of the most important tasks faced by scientists engaged in optimizing the parameters of the road network and the traffic flow streams. Such optimization can sometimes achieve organizational methods, by aligning the composition of traffic flow, its dispersal in time and space. However, this must be preceded by study Movement and the geometry of the road network.
Influence time interval in traffic flow bandwidth